An artificial neural network aided solution to the problem of voltage stability in power systems - Moghavvemi, M.; Jasmon, G.B. (ACTA Press, 1996)
This paper presents an artificial neural network (ANN) model for evaluating the voltage collapse point of a power system. Random changes in load level at all busbars in a distribution network will change the operating margin of the power system from a voltage stability point of view. The proposed method is able to almost accurately predict the voltage stability factor of a given distribution network resulting from either real or reactive power load changes or any other system parameter change.